Congenital Bilateral Absence of the Vas Deferens - Cai, Zhonglin; Li, Hongjun (Frontiers in Genetics, 2022)
Congenital bilateral absence of the vas deferens (CBAVD) is clinically characterized by the absence of the bilateral vas deferens, and its main clinical manifestation is infertility, accounting for 1–2% of male infertility cases. CBAVD may be accompanied by congenital abnormalities in the urogenital system and cystic fibrosis (CF)-related clinical manifestations. CBAVD can be a mild manifestation of CF, or it can be isolated. The main pathogenic mechanism of CBAVD is gene mutation, and CBAVD and CF have a common genetic mutation background. CFTR mutation is the main pathogenic cause of CBAVD and CF, and ADGRG2 mutation is the second most common cause. Although lack of the vas deferens in CBAVD patients causes infertility due to the inability to release sperm, the testes of CBAVD patients have spermatogenic function. Therefore, CBAVD patients can achieve fertility by sperm retrieval surgery and assisted reproductive technology (ART). However, gene mutations in CBAVD patients can have an impact on the ART outcome, and there is a risk of passing on gene mutations to the offspring. For CBAVD patients and their spouses, performing genetic counseling (which currently refers mainly to screening of CFTR mutations) helps to reduce the risk of genetic mutations being passed on to offspring and of offspring having CF with concomitant CBAVD.